PHOTOMETRIC STUDY OF A NEW X-RAY SOURCE -THE ECLIPSING POLAR RXJ 2107.9-0518 - Pavlenko, E. P. (Одеські астрономічні публікації, 2017)
The object RXJ 2107.9-0518 was discovered as a soft X-ray source at the space observatory ROSAT in 1990. Its X-ray spectrum is characteristic to the systems of the AM Her type thus the object was suspected to be a polar. The first photometric study of this object were obtained in 1992 independently at two observatories: in August-October by Schwope et al. at the 90-cm ESO telescope and in November-December by us at the 50-cm telescope of the Crimean Astrophysical Observatory. Our photometry confirmed the preliminary classification of this source as a polar with an orbital period of 125 minutes. The eclipses were detected with a duration of nearly 10 minutes and with depth ≥ 3.5m. It was found that the eclipsed emission source is shifted in respect to the line of centers at 32°. The morphology of the light curves is consistent with two active magnetic poles the power of which changes with time similar to BY Cam.